(NwYSOKO^ASTOTNYJ INDUKTIWNO(B-(NSWQZANNYJ PLAZMENNYJ RAZRQD W \MISSIONNOM SPEKTRALXNOM ANALIZE (B:s (NsBORNIK NAU^NYH TRUDOW (B/s - (NzILXBER[TEJN(B, (Nh(B.(Ni(B.s ((Nl(B. :s (NnAUKA(B. (NlENINGR(B. (NOTD(B-(NNIE(B,s, 1987)
(Nan sssr(B. (NoRDENA TRUDOWOGO KRASNOGO ZNAMENI IN(B-(NT HIMII SILIKATOW IM(B. (Ni(B.(Nw(B. (NgREBEN]IKOWAs
Keywords: (NsPEKTRALXNYJ ANALIZs